تنازع الاختصاص في عقود التجارة الإلكترونية - نجلاء, بن خليفة (جامعة الوادي - University eloued, 2022)
نلاحظ أن المشرع الجزائري لم ينص على قواعد الاختصاص بالنسبة للمنازعات المتعلقة بعقود التجارة الالكترونية واكتفى بالقواعد التقليدية لذا يستوجب وضع قواعد اختصاص تتعلق بالمعاملات التجارة الالكترونية كما يتعين وضع قواعد متعلق اختصاص محكمة المستهلك وهذا تماشيا مع تطور عقود التجارة الالكترونية. لا تكفي الحماية الدولية الخاصة بالمستهلك المقرر في قواعد الاختصاص القضائي الدولي حيث بالنظر إلى قواعد المجموعة الأوروبية اغلب التشريعات الوطنية نجد أن القواعد المقررة لحماية المستهلك بصفة عامة سواء كان مستهلكا الكترونيا أو تقليديا كان مقتصرا أعلى ضابطين من ضوابط الاختصاص وهما الضابط الإداري وضابط الموطن وبالتالي يجب الاعتراف تدعم النظام التحكيم الالكتروني في تسوية منازعات عقود التجارة الدولية حيث اثبت التحكيم الالكتروني كوسيلة من الوسائل البديلة لتسوية منازعات عقود التجارة الالكترونية. انه أفضل نهج يتبع في تسوية هاته المنازعات على اعتبار انه يقيم عبر نفس القنوات التي تتم عبرها هذه التجارة إلا وهي شبكة الاتصالات الالكترونية فالتحكيم يعتبر أهم مظاهر التطور الذي أفرزته الثورة المعلوماتية ويصبح انجح وسيلة لحل النزاعات إذ اقتنت بقوانين منظمة تحكمه واضحين له نصوص خاصة تزيل العقبات والمعوقات التي تحيط به، التي بعت هاجس ينقص من رغبة المتعاملين في اللجوء إليه والاستعانة به لفض منازعاتهم، فبالرغم منها سيتم بالسرعة ويوفر الجهد في الوقت لكنه يبقى كآلية فقط لتسوية النزاعات ولا يعتبر قانونا صارما يفرض على الجميع فيبقى مفيد بكثير من القيود خصوصا في الأنظمة الوطنية. We note that the Algerian legislator did not stipulate the rules of jurisdiction with regard to disputes related to electronic commerce contracts and was satisfied with the traditional rules, so it is necessary to establish rules of jurisdiction related to electronic commerce transactions, and rules related to the jurisdiction of the consumer court must be established, and this is in line with the development of electronic commerce contracts. The international protection of the consumer established in the rules of international jurisdiction is not sufficient. Looking at the rules of the European Community, most of the national legislation, we find that the rules established for consumer protection in general, whether electronic or traditional, were limited to the two highest jurisdictional controls, namely, the administrative officer and the domicile officer, and therefore must be recognized The system supports electronic arbitration in settling disputes in international trade contracts, as electronic arbitration has been proven as one of the alternative means for settling electronic trade contract disputes. It is the best approach to be followed in settling these disputes, considering that it resides through the same channels through which this trade takes place, which is the electronic communication network. And the obstacles surrounding it, which sold obsession, diminish the desire of dealers to resort to it and use it to resolve their disputes. Despite them, it will be done quickly and save effort in time, but it remains as a mechanism only for settling disputes. It is not considered a strict law imposed on everyone, so it remains useful with many restrictions, especially in national systems
مذكرة ماستر
Keywords: تنازع الاختصاص، عقود التجارة الإلكترونية، المستهلك الالكتروني، التحكيم الالكتروني; conflict of jurisdiction, e-commerce contracts, e-consumer, e-arbitration.